2009
DOI: 10.1111/j.1467-9876.2009.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Infectious Disease Parameters from Data on Social Contacts and Serological Status

Abstract: In dynamic models of infectious disease transmission, typically various mixing patterns are imposed on the so-called Who-Acquires-Infection-From-Whom matrix (WAIFW). These imposed mixing patterns are based on prior knowledge of agerelated social mixing behavior rather than observations. Alternatively, one can assume that transmission rates for infections transmitted predominantly through non-sexual social contacts, are proportional to rates of conversational contact which can be estimated from a contact survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 29 publications
4
125
0
Order By: Relevance
“…13]. In addition, various studies have shown that empirical contact data can successfully be applied in epidemiological models to replicate serological data [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…13]. In addition, various studies have shown that empirical contact data can successfully be applied in epidemiological models to replicate serological data [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For each of the vaccination options, the number of chickenpox and zoster episodes with and without vaccination is compared based on the direct costs (health care payer perspective) and consequences (life-years lost and Quality-Adjusted Life-Years (QALYs) lost) related to the episodes. The age-specific number of primary and breakthrough Age-specific force of infection Figure S2 • Social contact data from Belgium shown to fit best seroprevalence data [49][50][51] • Belgian VZV seroprevalence data 2003 (n = 3256, ages 0-80 y) 52 (Fig. S2) • Chickenpox and herpes zoster incidence data from Belgium 53…”
Section: Methodsmentioning
confidence: 98%
“…duration or frequency of interaction; presence or absence of physical contact) well-correlated with risk? Studies indicate that some measures of link properties generate better model fits to incidence data than others (Goeyvaerts et al, 2010) (see Challenge 2, above), but can we conclude that these measures of weight are more generally suitable? If we can robustly quantify link strength using available data for a pathogen of interest, we will be able to make network studies substantially more effective.…”
Section: Weighted Networkmentioning
confidence: 95%
“…The key challenge for the use of self-reported contact data to inform network models is to validate the relationship between reported contacts and infection. Modelling work has used different measured contact patterns to fit age-structured incidence or serology data (Goeyvaerts et al, 2010;Melegaro et al, 2011), but further work is needed to understand how to interpret the results. For example, if patterns of interactions involving physical contact provide the best fit to serological sampling, does this mean that infection actually spreads via physical contact, or just that such contacts provide a good proxy in a particular population?…”
Section: Proxy Measures Of Contactsmentioning
confidence: 99%